Menelusur Relasi Investasi, Konsumsi Rumah Tangga, Pengeluaran Pemerintah dan Sektor Pertambangan terhadap Pertumbuhan Ekonomi - Ruslam, Ruslam; Anwar, Andi Faisal (ICOR: Journal of Regional Economics, 2021)
Economic growth in Wajo Regency has been quite volatile and has slowed down every year. The problems faced are limited resources, while the need for funds for economic development in Wajo Regency is very large. From the contradictions that have occurred, it is the background for researchers to explore these problems. The purpose of this study is to determine whether there is an effect of investment, household consumption, government spending and the mining sector on economic growth in Wajo Regency. The type of research used in this research is quantitative research using multiple linear regression analysis through the help of the Eviews 10 software program. The data used are secondary data, in the form of time series data from 2008 to 2017 from BPS Wajo Regency, as well as reports, notes from other agencies, which are stored in archives. The research explains that the variables of investment, household consumption, government spending, and the mining sector have a significant and positive effect on economic growth. The implications of this study include that the government is expected to boost government spending as a trigger for investment entry and the private sector needs to be encouraged to utilize local resources so as to absorb a larger workforce to encourage more accelerated economic growth.Keywords: Growth, Investment, Consumption, Government Expenditures, Mining.